Kinematics of soccer instep kicking: a comparison of twodimensional and three-dimensional analysis - Nunome, H.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The influence of two- and three-dimensional filming procedures on the calculation of soccer instep kicking kinematics was examined in this study. The knee angular velocity calculated three-dimensionally was compared with the data obtained from the following two procedures: 1. the angular velocity vector was computed as a perpendicular component to the sagittal plane (2D projection); 2. the angular velocity was computed only from the two-dimensional coordinates (2D standard). A distorted changing pattern was produced by the 2D standard approach which was most likely caused by computing segmental angular velocities from quasi-planar projection. It is suggested that researchers treat with caution any comparisons in the literature between threedimensional angular kinematics and those computed two-dimensionally.